Increase success rate of weather forecasts for the airfield by integration of measurements of meteorological parameters of the atmosphere - E. A. Bolelov (Научный вестник МГТУ ГА, 2019)
Accuracy of aviation weather forecasts is one of the main indicators characterizing the quality of meteorological support of flights. A significant influence of the quality of meteorological support on flight safety and regularity is confirmed by the results of the annual tests conducted by the Federal Agency for Air Transport of Russia and "Aviamettelecom of Roshydromet". Currently, the quality of meteorological support of flights is still at a low level compared to countries that are recognized leaders in the aviation industry. To develop high-quality weather forecasts for the airfield weather service requires a large amount of information, which is based on the data of meteorological measurements and observations obtained by aerodrome meteorological systems. The lack of reliable information about the value of meteorological parameters of the atmosphere does not allow the weather man to form a qualitative weather forecast, so there are cases when the weather forecaster of the airfield weather service gives a reinsurance forecast. At the same time modern airfield meteorological systems have sufficiently advanced systems and devices for measuring the parameters of the atmosphere. The full use of all the advantages of these systems for the development of high-quality weather forecasts and, therefore, to improve their accuracy can be achieved through integrated processing of the meteorological information received. The most important characteristic of the atmosphere is the air temperature at aircraft flying altitudes. Reliable knowledge of the temperature profile largely determines the justification of weather forecasts and forecasts of dangerous weather events for aviation. The article considers, as an example, the algorithm of complex processing of information about the temperature profile in the aerodrome area, the structural scheme of the algorithm is obtained and te results of modeling the temperature profile and its complex evaluation are presented.